Battery-drive atmospheric pressure plasma jet for mass spectrometry applications. (August 2016) - Yang, Chao-Chi; Lin, Che-Hsin
Abstract: This paper presents a battery-drive atmospheric pressure plasma jet (APPJ) as the ion source for ambient mass spectrometry analysis of Chinese herbs. The AP plasma jet is generated under a dielectric barrier discharge (DBD) scheme in a low-cost glass tube for producing high density ions. Volatile specimens in solid Chinese herbs is directly analyzed using the mass spectrometry without delicate sample preparation procedures. The developed APPJ ion source can generate stable plasma for MS analysis under a low power consumption of 1.56 W. The generated ion intensity reaches 10 8 ion/cm 3 and the temperature of the APPJ ion source is lower than 50°C under normal operation. Experimental results indicate that the developed APPJ ion source can successfully detect the solid samples of ground coffee beans and a mixed sample of Chinese herbs. The characteristic ingredients for the solid samples can be rapidly ionized with the APPJ ion source and then detected by the mass spectrometer in seconds. The APPJ-MS system developed in the present study provides a simple yet high efficient way for detecting the ingredients of natural products under an ambient mass spectrometry apparatus.